2020
DOI: 10.1038/s41598-020-73413-5
|View full text |Cite
|
Sign up to set email alerts
|

The macroevolutionary landscape of short-necked plesiosaurians

Abstract: Throughout their evolution, tetrapods have repeatedly colonised a series of ecological niches in marine ecosystems, producing textbook examples of convergent evolution. However, this evolutionary phenomenon has typically been assessed qualitatively and in broad-brush frameworks that imply simplistic macroevolutionary landscapes. We establish a protocol to visualize the density of trait space occupancy and thoroughly test for the existence of macroevolutionary landscapes. We apply this protocol to a new phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 66 publications
3
39
0
Order By: Relevance
“…A Generalised Procrustes Superimposition (GPA) is then called to eliminate the size and positioning factors and then a Principal Component analysis (PCA) is applied on the GPA coordinates to produce morphospaces. Density-based macroevolutionary landscape are then produced using the method explained in Fischer et al [29]. Newly digitized models are deposited on Morphosource (https://www.morphosource.org/projects/000435369).…”
Section: High-density Geometric Morphometrics and Morphospace Occupationmentioning
confidence: 99%
“…A Generalised Procrustes Superimposition (GPA) is then called to eliminate the size and positioning factors and then a Principal Component analysis (PCA) is applied on the GPA coordinates to produce morphospaces. Density-based macroevolutionary landscape are then produced using the method explained in Fischer et al [29]. Newly digitized models are deposited on Morphosource (https://www.morphosource.org/projects/000435369).…”
Section: High-density Geometric Morphometrics and Morphospace Occupationmentioning
confidence: 99%
“…Comparative NMDS analyses were performed in ‘vegan’ v.2.5-6 (Oksanen et al 2018); graphical results from PCoA ecomorphospaces can be found in Supplementary Figure S1. Kernel 2D density estimates were used to visualise density-based macroevolutionary landscapes, plotted onto NMDS ecomorphospaces, following the methodology of Fischer et al (2020). Moreover, mandible length (proxy for body size) was used both in scaling datapoints to visually inspect the spread of large-sized mosasaurids, and additionally to compare the spread of body sizes in mosasaurids through the Campanian-Maastrichtian.…”
Section: Methodsmentioning
confidence: 99%
“…Marine ecosystems were dominated by reptiles during the entire Mesozoic (Motani 2002; Massare 1987; Bardet 2012; Scheyer et al 2014). Despite important turnovers at its base (Fischer et al 2017; 2020), the Late Cretaceous is no exception, as mosasaurid squamates rapidly diversified (Bardet et al 2008; 2007; Polcyn et al 2014), achieving a cosmopolitan distribution prior to the Campanian (c.83.5 Mya) (Bardet et al 2014; Polcyn et al 2014), and colonised several ecological guilds until their global extinction at the K/Pg boundary mass extinction (66 Mya) (Martin et al 2017). Prior to the Campanian, mosasaurid taxonomic richness saw a steep increase (Polcyn et al 2014), with speciation in the Western Interior Seaway (WIS) in central North America triggering a diversification during the so-called ‘Niobraran Age’ (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because skull shape in marine tetrapods is now known to be heavily influenced by ecomorphological convergence (e.g. Kelley & Pyenson, 2015;Fischer, 2016;Fischer et al, 2017Fischer et al, , 2020McCurry et al, 2017), these ratios are likely suboptimal to establish a stable taxonomy. Switching the taxonomy of Early Jurassic ichthyosaurians to apomorphy-based definitions is desirable and ongoing (Maisch & Matzke, 2000;Maisch, 2008Maisch, , 2010Martin et al, 2012;Lomax, 2016;Maxwell & Corteś, 2020;Swaby & Lomax, 2020), but still far from complete.…”
Section: Amongmentioning
confidence: 99%